Copper(I)-Catalyzed Sulfenylation of 1,3-Dicarbonyl Substrates with Disulfides under Mild Conditions - Zhao, Jingnan; Yang, Fan; Yu, Zongyi; Tang, Xiaofei; Wu, Yufeng; Ma, Cunfei; Meng, Qingwei (Synlett, 2019)
A copper(I) iodine catalyzed sulfenylation of 1,3-dicarbonyl substrates in the presence of MeCN is presented. Various β-keto esters and β-keto amide substrates can react with disulfides to afford their corresponding products in good to excellent yields. The notable features of this protocol include high atom economy, easy operation, mild reaction conditions, and excellent functional group tolerance.
Keywords: sulfenylation; disulfides; copper(I) iodide; β-keto esters; MeCN